CONDITION OF URBAN PHYSICAL ELEMENT IMPACT ON LAND SURFACE SUBSIDENCE IN PANGLIMA SUDIRMAN CORRIDOR, SURABAYA - Angger Sukma Mahendra; Eko Yuli Handoko; Akbar K (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2013)
Surabaya is the second largest city in Indonesia and has been categorized as a metropolitan. The development of Surabaya is quite fast in terms of physical development. That condition can be observed from the number of high rise buildings at the city centre corridors. One of the corridors in Surabaya city centre is Jalan Pang-lima Sudirman. The corridor is a high density mixed-used area, dominated by commercial and service such as office retails and hotels. From the measurement, it was found that land subsidence happened at Jalan Panglima Sudirman which in the future will impact on environmental physical condition at the location. Therefore, observation of certain items mainly related to urban physical element impact on land subsidence was important. The result expected is the visibility of urban physical element impact in land subsidence at the corridor of Jalan Panglima Sudirman Surabaya.